2019
DOI: 10.1002/ps.5515
|View full text |Cite
|
Sign up to set email alerts
|

20‐Hydroxyecdysone enhances Immulectin‐1 mediated immune response against entomogenous fungus in Locusta migratoria

Abstract: Background Entomogenous fungi are important factors in biological control, but innate immunity of insects restricts the efficiency of fungus infection. 20‐hydroxyecdysone (20E) is involved in regulating the immune response of insects. Our previous studies have revealed that 20E enhances the expression of antibacterial peptides in the worldwide pest Locusta migratoria. However, the mechanism by which 20E controls innate immunity against entomogenous fungi is still unknown. Results In the present study, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Moreover, it has been reported that phytoecdysteroids improve skin quality by accelerating the healing of wounds and burns [ 36 , 37 ].Several studies [ 38 ] have claimed associations between Malassezia restricta lipase and SD. In light of this, ecdysteroids, especially 20-hydroxyecdysone, probably enhance antifungal immunity, resulting in a reduction of disease symptoms [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been reported that phytoecdysteroids improve skin quality by accelerating the healing of wounds and burns [ 36 , 37 ].Several studies [ 38 ] have claimed associations between Malassezia restricta lipase and SD. In light of this, ecdysteroids, especially 20-hydroxyecdysone, probably enhance antifungal immunity, resulting in a reduction of disease symptoms [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Spodoptera exigua, Se-sPLA2A has been reported to be regulated by pyriproxyfen, a juvenile hormone analog [12]. Moreover, a number of studies demonstrate that 20-hydroxyecdysone can play an important role in the metamorphosis process [20,22,27,28]. These results suggest that the PLA2A family may have a crucial biological role in the developmental process of insects.…”
Section: Discussionmentioning
confidence: 96%
“…After entering the haemocoel, it is necessary to overcome the host's innate immune defense response first and then effectively obtain the nutrients in the host for growth and reproduction. This ultimately leads to the death of the host insect [7,19]. Pathogenic fungi are induced by the secretions of insect body walls, hemolymph or plant roots, and there are great differences in the types and levels of gene expression.…”
Section: Discussionmentioning
confidence: 99%